A consensus conference to define the utility of advanced infectious disease diagnostics in solid organ transplant recipients. Issue 12 (27th July 2022) - Azar, Marwan M.; Turbett, Sarah; Gaston, David; Gitman, Melissa; Razonable, Raymund; Koo, Sophia; Hanson, Kimberly; Kotton, Camille; Silveira, Fernanda; Banach, David B.; Basu, Sankha S.; Bhaskaran, Archana; et al.
Abstract : The last decade has seen an explosion of advanced assays for the diagnosis of infectious diseases, yet evidence‐based recommendations to inform their optimal use in the care of transplant recipients are lacking. A consensus conference sponsored by the American Society of Transplantation (AST) was convened on December 7, 2021, to define the utility of novel infectious disease diagnostics in organ transplant recipients. The conference represented a collaborative effort by experts in transplant infectious diseases, diagnostic stewardship, and clinical microbiology from centers across North America to evaluate current uses, unmet needs, and future directions for assays in 5 categories including (1) multiplex molecular assays, (2) rapid antimicrobial resistance detection methods, (3) pathogen‐specific T‐cell reactivity assays, (4) next‐generation sequencing assays, and (5) mass spectrometry‐based assays. Participants reviewed and appraised available literature, determined assay advantages and limitations, developed best practice guidance largely based on expert opinion for clinical use, and identified areas of future investigation in the setting of transplantation. In addition, attendees emphasized the need for well‐designed studies to generate high‐quality evidence needed to guide care, identified regulatory and financial barriers, and discussed the role of regulatory agencies in facilitating research and implementation of these assays. Findings and consensus statements are presented. Abstract : This meeting report summarizes findings from an AST‐sponsored consensus conference to define best practice uses, unmet needs and future directions for advanced infectious diseases diagnostics in solid organ transplant recipients.